Association Between School-Level Prevalence of Electronic Cigarette Use and Student-Level Use Behaviors, Pre-Use Intentions, and Risk Perceptions: Evidence From the 2014 US National Youth Tobacco Survey. Issue 2 (27th December 2016) - Lippert, Adam M
Abstract: Background: Adolescent electronic cigarette ("e-cigarette") use tripled in recent years, yet little is known about the school-level correlates of teenage e-cigarette use, harm and risk perceptions, or pre-use intentions to use. Methods: Multilevel regression and 2014 National Youth Tobacco Survey data were used to assess school-level e-cigarette prevalence and person-level e-cigarette use as well as age at initiation and frequency of use (among initiates), expectations for future use (among abstainers), and perceived e-cigarette addictivity and harm. Results: Lifetime use was higher among students in medium- (odds ratio [OR] = 2.30, 95% confidence interval [CI] = 1.82, 2.89) and high- (OR = 4.66, 95% CI = 3.67, 5.90) versus low-use schools. Past 30-day use followed a similar pattern. Multilevel ordinal logistic models revealed that initiates from high-use schools reported more days of use in the past month (OR = 2.25, 95% CI = 1.52, 3.33) and higher age-at-first-use (OR = 1.45, 95% CI = 1.08, 2.00) than students at low-use schools. Expectations for future use were higher among abstainers from medium- and high- versus low-use schools, and among all students, perceived addictivity and harm caused by e-cigarettes were lower in medium- and high- versus low-use schools. Conclusion: School context is associated with multiple dimensions of e-cigarette use, pre-use intentions, and perceptions of e-cigarette health risks. Implications: The current study demonstrates a link between school prevalence of e-cigarette use and student-level use, as well as perceived risks of e-cigarette use, age of initiation and frequency of use among users, and intentions to use among abstainers. Health communication and prevention initiatives should target school social environments to promote nicotine abstinence and a culture of health.